Irreproducible positive results on the Cobas AmpliPrep/Cobas TaqMan HIV‐1 Qual test are different qualitatively from confirmed positive results. Issue 1 (17th October 2013) - Maritz, Jean; van Zyl, Gert U.; Preiser, Wolfgang
Abstract Criteria that define low positive results on the COBAS® AmpliPrep/COBAS® TaqMan (CAP/CTM) HIV‐1 Qual test as inconclusive have been adopted by all academic centres in South Africa that conduct infant HIV PCR, following previous investigations that showed poor specificity of these results. Retesting all inconclusive specimens has considerable cost implications. Therefore, it was attempted to characterise such inconclusive results, by comparing those that prove to be either negative or positive on follow‐up testing. This retrospective, laboratory‐based study found that 193 of 211 (91.5%) patients with previous inconclusive results (defined as reported positive by CAP/CTM but with cycle threshold [Ct] values of >32 and/or fluorescence intensity [FI] values of <5) tested negative and only 18 (8.5%) tested positive using independently obtained follow‐up samples after a median of 28 days. The only significant independent predictor of a later positive result was a higher FI value (3.326 vs. 0.495, P < 0.0001), whereas Ct values were not predictive independently. Specimens from patients negative on follow‐up testing differed qualitatively from specimens that proved to be true positives. As the lower FI values in false‐positive compared to true‐positive results probably are indicative of a non‐specific signal, the incorporation of stringent amplification slope criteria in the assay's test definition file may improve correct classification and thus reduce the need for repeat testing of a large number of inconclusive specimens. J. Med. Virol. 86:82–87, 2014. © 2013 Wiley Periodicals, Inc.